Design and Evaluation of Osmotic Drug Delivery System of Efonidipine - Srilatha, Ch (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: The aim of the present research work was to design an elementary osmotic pump (EOP) of efonidipine hydrochloride (EFH), a biopharmaceutical classification system class II drug. Materials and Methods: To enhance the solubility of EFH by novel co-amorphous solid dispersion technique, drug-loaded solid dispersion composed of efonidipine/co-former at a weight ratio of 1:1, 1:2, 1: 4, 1:8, and 1:12 was prepared by fusion method. Based on the drug release profiles, efonidipine/pimelic acid dispersions were optimized. To formulate the core tablets, sodium chloride and mannitol were used as osmotic agents. Four distinct core compositions, labeled as EF1 through EF4, were prepared following a 22 full factorial design approach to systematically optimize the drug’s release profile, and four different coating compositions (a, b, c, and d) were applied to four distinct formulations (EF1 to EF4) resulting in a total of 16 formulations. EOP tablets were prepared by applying a semipermeable membrane, cellulose acetate with an orifice on the surface. Results and Discussion: Evaluation of the prepared EOP tablets showed satisfactory results, with all 16 formulations exhibiting complete release of efonidipine over approximately 24 h. The steepest ascent method was employed to determine the appropriate quantities, and optimized formulation was designed to release the drug in a controlled manner over a 24-h period. The study demonstrated that the main factor affecting drug release was osmosis alone, and factors such as agitation and stagnant conditions had no significant impact on drug release. As a result, a successful controlled drug delivery system for efonidipine over a 24-h duration was developed using an optimized technique based on a 24 factorial design. In vivo study was performed in New Zealand white rabbits and various parameters such as Cmax, tmax, AUC, AUMC, and MRT were calculated and compared with that of marketed tablet. Conclusion: In summary, efonidipine osmotic pump tablets presented controlled release in vitro, high bioavailability in vivo and a good in vitro-in vivo correlation.